Gonadal Maturation and Spawning of Barred Loach (Nemacheilus fasciatus) Induced by Topical Gill Hormone Application - Budi, Darmawan Setia; Ardiyan, Buyung Raga; Rahmawan, Dani Bagus; South, Josie; Fasya, Arif Habib; Mukti, Akhmad Taufiq (Universitas Airlangga, 2024)
Barred loach Nemacheilus fasciatus are unable to reproduce naturally in captivity due to the lack of environmental cues and gonadal maturation occurs slower than in the wild. To optimize breeding procedures for this fish species, we determined whether hormone application via the gills was an effective process and assessed hormone dosage treatments. Oodevâ„¢ was used to induce gonadal maturation and Ovaprimâ„¢ was used to induce spawning via a topical gill approach. Multiple maturation parameters such as gonadal-somatic index (GSI) and hepatosomatic index (HSI), fecundity, and egg diameter; and spawning parameters such as latency period, egg produce, fertilization rate (FR), hatching rate (HR), survival rate (SR) were recorded and compared between the hormone dosage treatments and control treatment. Both the Oodevâ„¢ gonadal maturation induction and Ovaprimâ„¢ spawning induction were effectively applied to barred loach via topical gill application. Gonadal maturation parameters were positively correlated with dosage and all were significantly different. Fry survival rate was not different between doses. The optimal dose of Oodevâ„¢ (0.75 µL/g fish) resulted in male GSI of 5.334 ± 0.320%, female GSI of 15.501 ± 0.675%, male HSI of 0.416 ± 0.023%, female HSI of 1.670 ± 0.104%, egg fecundity 4584.20 ± 493.216 eggs, egg diameter 0.964 ± 0.0151 mm. Ovaprimâ„¢ optimal dosage (3.00 µL/g female and 1.50 µL/g male) was resulted latency period 11.05 ± 0.52 hours, egg produced 3504.83 ± 358.57, FR 96.77 ± 0.88%, HR 83.62 ± 3.78%, and SR 91.44 ± 2.53%.